Regulation of the lending market and prospects of financial sector stabilization in Ukraine - Sodoma, R.; Cherevko, H.; Krupiak, I.; Andrusiak, H.; Brodska, I.; Shmatkovska, T. (My University, 2021)
Current issues of non-bank lending by financial companies and the vision of the future regulation of their activities outline in detail the developments set out in this article. Changes in the volume of lending in the non-banking financial market are analyzed. The analysis of the concentration level of loans by the amount of concluded agreements is carried out. The future vision and mission of the financial sector of the economy are formed. Criteria for assessing the required degree of supervision of a credit company are defined. In the study, we used general and specific economic methods, as well as a basic research approach, which allowed us to determine the economic nature of the financial sector and the scope of lending to agricultural enterprises.The goals of realization of an economic growth strategy for the perspective period for the achievement of the European standards in the financial market are offered. Financial support for current activities and promising economic development in Ukraine still remains a significant problem. Expanding access to financial resources of agricultural entities may be one of the factors for the development of Ukraine’s economy. The main goal of the National Bank is to introduce a risk-oriented approach in the licensing and supervision procedures of the non-bank lending market, which will allow it to develop and ensure compliance with the rights and interests of customers. It is proposed to maintain the procedure for agreeing significant participation for financial companies as a key element in verifying the transparency of ownership structures and the impeccable business reputation of owners. The scientific novelty of the obtained results is represented by a set of theoretical and practical aspects of the study, namely proposals for the current state of lending and recommendations for supervision in the financial market of Ukraine.
Keywords: lending; stabilization; financial sector; financial sector regulators; non-bank lending; G19; 332.85